Hedonistic Life Reflected In Anne Stuart's Ruthless Novel (2010): A Sociological Approach - Kurniawati, Endah; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This study is about hedonistic life in Ruthless novel. The problem of the study is how hedonistic life is reflected in Ruthless novel. The object of the study is "Ruthless" novel by Anne Stuart. It uses sociological approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel and the secondary data is other materials related to the study. The result of the study shows the following conclusion. Based on the analysis it shows that there is a close relation between the novel and the social reality of American society at the late twentieth century and the early of twenty first century. Anne Stuart wants to tell a hedonistic life in Ruthless novel.